Responden Peserta Didik dan Guru terhadap Kemampuan Berpikir Kritis SMAN 14 Pekanbaru - Santika, Rosi; Ferazona, Sepita; Hidayati, Nurkhairo (Universitas Cokroaminoto Palopo, 2024)
This study aims to analyze the critical thinking skills of students of SMA Negeri 14 Pekanbaru based on gender differences in the context of biology learning. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The research sample included all grade XI students, consisting of 69 male students and 81 female students. The results of the study indicate that teachers have used critical thinking-based questions in learning evaluations, although they have not been fully guided by clear indicators. Based on interviews, students from science classes find it easier to solve questions than students from business classes, who find the questions more difficult. The conclusion of this study is that although critical thinking skills have begun to be applied, the development of structured indicators and adjustments to the level of difficulty of questions need to be done to support students' critical thinking skills optimally.